New insights into the molecular epidemiology and population genetics of Schistosoma mansoni in Ugandan pre-school children and mothers. - Martha Betson; Jose C Sousa-Figueiredo; Narcis B Kabatereine; J Russell Stothard (Public Library of Science (PLoS), 2013)
Significant numbers of pre-school children are infected with Schistosoma mansoni in sub-Saharan Africa and are likely to play a role in parasite transmission. However, they are currently excluded from control programmes. Molecular phylogenetic studies have provided insights into the evolutionary origins and transmission dynamics of S. mansoni, but there has been no research into schistosome molecular epidemiology in pre-school children. Here, we investigated the genetic diversity and population structure of S. mansoni in pre-school children and mothers living in lakeshore communities in Uganda and monitored for changes over time after praziquantel treatment. Parasites were sampled from children (<6 years) and mothers enrolled in the longitudinal Schistosomiasis Mothers and Infants Study at baseline and at 6-, 12- and 18-month follow-up surveys. 1347 parasites from 35 mothers and 45 children were genotyped by direct sequencing of the cytochrome c oxidase (cox1) gene. The cox1 region was highly diverse with over 230 unique sequences identified. Parasite populations were genetically differentiated between lakes and non-synonymous mutations were more diverse at Lake Victoria than Lake Albert. Surprisingly, parasite populations sampled from children showed a similar genetic diversity to those sampled from mothers, pointing towards a non-linear relationship between duration of exposure and accumulation of parasite diversity. The genetic diversity six months after praziquantel treatment was similar to pre-treatment diversity. Our results confirm the substantial genetic diversity of S. mansoni in East Africa and provide significant insights into transmission dynamics within young children and mothers, important information for schistosomiasis control programmes.